TROUBLESHOOTING STEPS AND SOLUTION INSPECTION METHODS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Taking into account the characteristic feature of mathematics (abstractness of concepts and logical confirmation of ideas), the content of the educational material, the content of the mathematics course studied in general secondary schools, academic lyceums and vocational colleges can be divided into two parts: theoretical material and mathematical problems. From the methodological point of view (from the point of view of the form of knowledge), theoretical material as concepts and their definition, ideas (theorems, properties, signs, etc.), algorithms (rules, formulas, etc.), various mathematical methods (direct and it is given by direct proof, by the method of coordinates and vectors, equations and inequalities, proof by inverse, etc.).